Multiple system atrophy and CAG repeat length: A genetic screening of polyglutamine disease genes in Italian patients. (21st June 2018) - Mongelli, Alessia; Sarro, Lidia; Rizzo, Elena; Nanetti, Lorenzo; Meucci, Nicoletta; Pezzoli, Gianni; Goldwurm, Stefano; Taroni, Franco; Mariotti, Caterina; Gellera, Cinzia
Highlights: MSA phenotype shows a challenging overlap with dominant polyglutamine diseases. Utility of polyQ genetic screening in Italian MSA population. MSA-C had higher percentage of longer normal SCA1 alleles compared to other groups. One MSA-C patient carried an expanded SCA2 allele, suggesting possible misdiagnosis. Abstract: Multiple system atrophy (MSA) is an adult onset, progressive, neurodegenerative disorder of unknown etiology characterized by autonomic dysfunction, parkinsonism (MSA-P) and cerebellar ataxia (MSA-C). The phenotypic spectrum may present overlapping features with other neurodegenerative diseases, particularly the autosomal dominant inherited polyglutamine disorders. To investigate the possible contribution of CAG expansions in the MSA phenotype, we analyzed the triplet repeat length in the autosomal dominant causative genes for spinocerebellar ataxia (SCA) type 1, 2, 3, 6, 7, 17, dentatorubral-pallidoluysian atrophy (DRPLA) and Huntington disease (HD) in a cohort of 246 Italian MSA patients. As comparison, 223 controls were also analyzed. The alleles were classified on the basis of CAG repeat length as "normal", "intermediate" or "expanded" according to literature. The MSA patients (101 men/145 women) had a mean age at onset of 58 years and a mean age at genetic testing of 63 years. MSA-C patients had significantly younger age at onset and at examination in comparison to MSA-P (p < 0.0001). We identified a SCA1 intermediate allele in a MSA-C subject (36 CAG), a SCA2 intermediate allele in a MSA-P patient (31 CAG), and a pathologically expanded SCA2 allele (36 CAG) in a patient initially misdiagnosed as MSA-C. No intermediate or expanded SCA alleles were detected in controls. The distribution of CAG repeat length was similar among groups except for SCA1 gene that showed a higher percentage of longer normal alleles in MSA-C as compared to MSA-P and controls (p < 0.0001). This study supports the utility of polyQ genetic testing in the differential diagnosis of MSA, and may suggest a possible role of SCA1 repeat length as risk factor for MSA-C. SCA1 and SCA2 genetic screening is recommended in MSA Italian patients.